The Effect of Picture Series through Retelling Story on Students’ Speaking Narrative at Elementary School: Pengaruh Picture Series melalui Retelling Story pada Narasi Berbicara Siswa di Sekolah Dasar - Teti Hertanti; Dian Rahma Santoso (Academia Open, 2022)
The objective of this research is to know how effect picture series on students’ ability in retelling narrative story. The research methodology used in this research is pre experimental design. The result is used to know the effect of picture series through retelling story on students’ speaking narrative. This research was conducted at MTS Muhammadiyah 1 Taman. The sample was chosen from VIII B based on pre observation and pre interview students score that is the lowest of all classes. In collecting the data, this research use pretest and posttest. The test was asked students to perform speak in front of the class in minimal 5 minutes with retell story from picture series. In analysis the data the researcher scoring the score of pretest and posttest, after that drawing the conclusion with computerized of Ms. Excel. Through the analysis of the findings of pre-test and post-test, it can be concluded that picture series gave the positive effect toward students’ speaking ability, this can be seen from the improvement in the score of students in the course. Picture series leads the students’ being self-critical, because they can evaluate their mistakes by their selves. The result of the data revealed after implementing picture series, the students’ speaking scores were significantly better and well improved (the mean of pre-test = 72,43 and post-test = 77,79).